Role for IL-1 Family Cytokines in Fungal Infections - Griffiths, James S.; Camilli, Giorgio; Kotowicz, Natalia K.; Ho, Jemima; Richardson, Jonathan P.; Naglik, Julian R. (Frontiers in Microbiology, 2021)
Fungal pathogens kill approximately 1.5 million individuals per year and represent a severe disease burden worldwide. It is estimated over 150 million people have serious fungal disease such as recurrent mucosal infections or life-threatening systemic infections. Disease can ensue from commensal fungi or new infection and involves different fungal morphologies and the expression of virulence factors. Therefore, anti-fungal immunity is complex and requires coordination between multiple facets of the immune system. IL-1 family cytokines are associated with acute and chronic inflammation and are essential for the innate response to infection. Recent research indicates IL-1 cytokines play a key role mediating immunity against different fungal infections. During mucosal disease, IL-1R and IL-36R are required for neutrophil recruitment and protective Th17 responses, but function through different mechanisms. During systemic disease, IL-18 drives protective Th1 responses, while IL-33 promotes Th2 and suppresses Th1 immunity via a complicated mechanism. The IL-1 family represents an attractive anti-fungal immunotherapy target. There is a need for novel anti-fungal therapeutics, as current therapies are ineffective, toxic and encounter resistance, and no anti-fungal vaccine exists. Furthering our understanding of the IL-1 family cytokines and their complex role during fungal infection may aid the development of novel therapies. As such, this review will discuss the role for IL-1 family cytokines in fungal infections.